GENERAL PHYSICAL FITNESS INDICATORS OF BOXERS 11-12 YEARS OLD - Tajibayev Soyib Samijanovich; Nabiyev Shahboz Ubaydulla o‘g‘li; Qahhorjonov Abdulaziz Shuhrat o‘g‘li (Journals Park Publishing, 2022)
The article examines the general physical fitness indicators of boxers aged 11-12 years engaged in primary training groups of children's and youth sports schools.
Keywords: Physical training, physical qualities, strength, speed, agility